Do the regulations of the Electoral Code contradict with the Bulgarian Constitution as they provide for calculating “ex-lege” the vote of the party ballots without any preference in favor of the list leader - Slavov, Peter (Law Journal of New Bulgarian University, 2022)
This article provides an analysis of the possible contradiction with the Constitution of the regulations in the Bulgarian Election Code creating a “privilege” for the list leaders in municipal elections as well as for MPs, who are entitled to, according to art. 278 (5) and art. 437 (5), along with their own preferential vote, also to receive the party ballots without any preference in them. Thus, it is obvious that there is a privileged position of these list leaders (while the other candidates are being discriminated against), which puts the aforementioned regulations of the Election Code in contradiction with art. 6 (2) of the Bulgarian Constitution – prohibition of privileges or discrimination, art. 10 – common, equal, direct voting right and art. 4 (1) – rule of law.